Identity Functioning and Eating Disorder Symptomatology: The Role of Cognitive Emotion Regulation Strategies - Verschueren, Margaux; Claes, Laurence; Palmeroni, Nina; Raemen, Leni; Buelens, Tinne; Moons, Philip; Luyckx, Koen (Frontiers in Psychology, 2021)
Introduction. Adolescence is the most critical life period for the development of eating disorder (ED) symptomatology. Although problems in identity functioning and emotion dysregulation have been proven important risk and maintaining factors of ED symptomatology, they have never been integrated in a longitudinal study. Methods. The present study is part of the Longitudinal Identity research in Adolescence (LIA)-study and aimed to uncover the temporal interplay between identity functioning, cognitive emotion regulation, and ED symptomatology in adolescence. A total of 2162 community adolescents (Time 1: 54% female; Mage=14.58, SD=1.88, range=10-21 years) participated at three measurement points with one-year intervals. They reported on identity functioning (identity synthesis and identity confusion), cognitive emotion regulation (rumination, catastrophizing, and positive reappraisal), and ED symptomatology (drive for thinness and bulimia symptoms). Results. Cross-lagged paths could be fixed for boys and girls and showed bidirectional associations between both dimensions of identity functioning and both rumination and catastrophizing over time. Similarly, these maladaptive cognitive emotion regulation strategies were bidirectionally related to ED symptomatology over time. Finally, indirect pathways pointed to bidirectional associations between both dimensions of identity functioning and bulimia symptoms through rumination and catastrophizing. Only unidirectional associations emerged for drive for thinness and almost no cross-lagged associations were found with positive reappraisal. Conclusion. The present study demonstrates that identity confusion may contribute to the development of ED symptomatology in adolescence through cognitive emotion dysregulation. It also reveals that these ED symptoms hamper identity development through emotion dysregulation. These results stress the importance of targeting both identity functioning and cognitive emotion regulation in the prevention and intervention of ED symptoms.